Design, Synthesis and Evaluation of N-pyrazinylbenzamides as Potential Antimycobacterial Agents - Zitko, Jan; Mindlová, Alžběta; Valášek, Ondřej; Jand'ourek, Ondřej; Paterová, Pavla; Janoušek, Jiří; Konečná, Klára; Doležal, Martin (Molecules (Basel, Switzerland), 2018)
Three series of N-(pyrazin-2-yl)benzamides were designed as retro-amide analogues of previously published N-phenylpyrazine-2-carboxamides with in vitro antimycobacterial activity. The synthesized retro-amides were evaluated for in vitro growth inhibiting activity against Mycobacterium tuberculosis H37Rv (Mtb), three non-tuberculous mycobacterial strains (M. avium, M. kansasii, M. smegmatis) and selected bacterial and fungal strains of clinical importance. Regarding activity against Mtb, most N-pyrazinylbenzamides (retro-amides) possessed lower or no activity compared to the corresponding N-phenylpyrazine-2-carboxamides with the same substitution pattern. However, the active retro-amides tended to have lower HepG2 cytotoxicity and better selectivity. Derivatives with 5-chloro substitution on the pyrazine ring were generally more active compared to their 6-cloro positional isomers or non-chlorinated analogues. The best antimycobacterial activity against Mtb was found in N-(5-chloropyrazin-2-yl)benzamides with short alkyl (2h: R² = Me; 2i: R² = Et) in position 4 of the benzene ring (MIC = 6.25 and 3.13 µg/mL, respectively, with SI > 10). N-(5-Chloropyrazin-2-ylbenzamides with hydroxy substitution (2b: R² = 2-OH; 2d: R² = 4-OH) on the benzene ring or their acetylated synthetic precursors possessed the broadest spectrum of activity, being active in all three groups of mycobacterial, bacterial and fungal strains. The substantial differences in in silico calculated properties (hydrogen-bond pattern analysis, molecular electrostatic potential, HOMO and LUMO) can justify the differences in biological activities between N-pyrazinylbenzamides and N-phenylpyrazine-2-carboxamides.
Keywords: antibacterial; Mycobacterium tuberculosis; buněčné linie; mikrobiální testy citlivosti; cytotoxicity; techniky syntetické chemie; Molecular Structure; Structure-Activity Relationship; lidé; Anti-Bacterial Agents; Chemistry Techniques, Synthetic; Cell Line; tuberculosis; Models, Molecular; pyrazinamide; molekulární struktura; Microbial Sensitivity Tests; Benzamides; molekulární modely; benzamidy; racionální návrh léčiv; linker; antimycobacterial; Drug Design; vztahy mezi strukturou a aktivitou; antifungal; Cell Survival; viabilita buněk; antibakteriální látky; retro-amide; Humans